2009
DOI: 10.1098/rspb.2009.0586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urban noise on song and response behaviour in great tits

Abstract: Acoustic communication is fundamental in avian territory defence and mate attraction. In urban environments where sound transmissions are more likely to be masked by low-frequency anthropogenic noise, acoustic adaptations may be advantageous. However, minor modifications to a signal could affect its efficacy. While recent research has shown that there is divergence between songs from noisy and quiet areas, it is unknown whether these differences affect the response to the signal by its receivers. Here, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 45 publications
8
134
3
1
Order By: Relevance
“…However, noise in natural environments covers a wide frequency range [33] and therefore may not exert a strong directional selection pressure for higher frequencies across multiple geographical locations in the same way as urban noise, which is consistent between cities, and is almost exclusively concentrated in the lower frequency bands. to habitat [15,34]. However, frequency shifts in urban environments have also been observed in taxa that do not learn their vocalizations, such as non-passerine birds [23], and the southern brown tree frog (Litoria ewingii; [21]).…”
Section: Discussion (A) Song Frequenciesmentioning
confidence: 99%
“…However, noise in natural environments covers a wide frequency range [33] and therefore may not exert a strong directional selection pressure for higher frequencies across multiple geographical locations in the same way as urban noise, which is consistent between cities, and is almost exclusively concentrated in the lower frequency bands. to habitat [15,34]. However, frequency shifts in urban environments have also been observed in taxa that do not learn their vocalizations, such as non-passerine birds [23], and the southern brown tree frog (Litoria ewingii; [21]).…”
Section: Discussion (A) Song Frequenciesmentioning
confidence: 99%
“…During energetically demanding periods in a bird's life, increasing vigilance can reduce survival because of increased starvation risk (27). In contrast to song masking, which can be partially overcome by frequency shifting (28), release from masking is not possible for auditory cues necessary for aural vigilance (7). With limited auditory information, animals must resort to other methods such as visual scans to compensate for the increase in perceived predation risk, perhaps driven by masking of communication calls and predator-generated sounds (26,29).…”
Section: Significancementioning
confidence: 99%
“…they increase the amplitude of their vocalizations in response to an increase in background noise (reviewed in [19]), which is used to communicate in the presence of anthropogenic noise [20]. It is also often observed that birds sing at higher frequencies at noisy locations [21][22][23][24][25], which is probably the result of vocal plasticity [26][27][28].…”
Section: Introductionmentioning
confidence: 99%